The development risk clause in Colombian product liability law (2014)
This essay explores, from the perspective of comparative law, the notion of development risk as grounds for the exclusion of product liability under Colombian law. Based on the notions of 'default' and 'exclusion of liability' (or defense), the authors analyze the scope of the innovations incorporated by the products liability regime in a system that is based on the code of Andrés Bello.